Zalesienie użytków rolnych jako element zrównoważonego rozwoju obszarów wiejskich - Woźniak, Marian; Walenia, Alina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The scenery is not only a part of space that we should look at, it is rather a world among which we stand, taking the perspective of its creation. The scenery have played an important role in history and memory of societies' culture, and a very important element of sustainable development is proper forest management. Primeval scenery (i.e. forest), which to the smallest degree was touched by the "creative" hand of a man, is a crucial element of balance of a Polish village. Forests serve productive functions, but also, or maybe first of all fulfillment of needs, psychological, cultural, spirit and health functions. In the paper, there was also pointed out the matter of financial support in the process of afforestation of farmlands of low usefulness for agriculture as well as its impact on multifunctional and sustainable development of a country. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 157-163